The Commodification of Islam in Halal Cosmetics Advertising in Indonesia (Judith Williamson Semiotics Analysis) - Mutiah, Isnaini Umi; Andreas, Rino; Mahardika, Dzikrina Aqsha; Setiawan, Azizah Nafabilla; Septiyanti, Nisa Dwi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The purpose of this paper is to explain the commodification of Islam in the advertisement of Wardah cosmetic products through Judith Williamson's semiotic analysis. Advertising as a communicative medium aims to influence consumers by constructing the dominant discourse in Muslim society. One of them is seen in Wardah's beauty product advertisement by building Islamic discourse. This qualitative research uses the advertising semiotics method which examines the relation between signifier and signified in an object. The researcher analyzed the scenes in five Wardah advertisements. The results show that "Wardah TV commercial" embeds Islamic discourse through the concept of "halal'' cosmetics through text and audio-visual components. This Islamic discourse was built through language and then commodified as a product with a "halal" label attached to Wardah's commodities, namely using natural alcohol, not being contaminated with prohibited materials, and the production process in accordance with Islamic procedures. Furthermore, Wardah's advertisement featured multi-talented artists Dewi Sandra and Natasha Rizki, who were known as hijrah models, singers, and film actresses. Thus, Wardah succeeded in "borrowing" the meaning of popularity, Muslim youth, and achievement so that the product obtains a significant meaning based on the artist's reference system. The decommodification process looks at the ideology that is hidden and played by industrial interests in the segment of Muslim society in Indonesia.